Acute Respiratory Infections (Pneumonia) Incidence Rate in Children due to Climate Variables and Air Quality in Bogor - Revia Muharrami; Rini Hidayati; Ana Turyanti (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2021)
Pneumonia is the respiratory infection disease, which is influenced by climatic variables and air quality. However, little is known how rainfall and air humidity influence on the disease situated in a high traffic density such as in Bogor, Indonesia. The research aims to analyze the influences of rainfall, air humidity, and air pollution on the incidence rate of pneumonia under 5-year old children in Bogor. We used statistical approaches namely correlation and principal component analysis and combined with chart analysis to identify the influences. Our results revealed that high rainfall (high relative humidity) improved air quality by lowering the concentration of particulate matter. But, the indoor microorganism growth would increase, therefore it affects the incidence rate of pneumonia under 5-year old children, especially in transition season from wet to dry. In dry season, high concentration of particulate matter in the air would increase the incidence rate of pneumonia. Other findings showed that climate (through humidity) and particulate matters have regulated the pneumonia incidence rate in Bogor. The rate was higher under high humidity. On other hand, in transition from dry to wet season, concentration of particulate matters was more dominant to influence the incident rate.